Introduction of Alley Cropping - Sugeng Parmadi (Forum Geografi, 1998)
One of the efforts to preserve the sources of vegetarian, soil, and water is to rehabilitate the land and soil conservation. The aim of this rehabilitation is increasing and maintaining the produtivity of the land, so it can be preserved and used optimally. Therefore, it is necessary to a  develop a variety of good soil conservation, such as vegetative method and civil engineering. To find an appropriate technology, so it is necessary to develop some alternatives of soil conservation technique that are mainly implemented at dry land with its slope of more than 15% in the upstream area of discharge. One of the most suitable soil conservation technique today is Alley Cropping. Based on the research (trial and error) in some areas, Alley Cropping could really provide a positive result in terms of erotion controlling and running off and maintain the land productivity. In addition, the technique is more easly operated and spends a cheaper cost than making a bench terrace.